2011
DOI: 10.1007/s00253-011-3204-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of the carbon oxidation-reduction state on organic pollutant biodegradation in algal–bacterial photobioreactors

Abstract: The influence of the carbon oxidation-reduction state (CORS) of organic pollutants on their biodegradation in enclosed algal-bacterial photobioreactors was evaluated using a consortium of enriched wild-type methanotrophic bacteria and microalgae. Methane, methanol and glucose (with CORS −4, −2 and 0, respectively) were chosen as model organic pollutants. In the absence of external oxygen supply, microalgal photosynthesis was not capable of supporting a significant methane and methanol biodegradation due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…(4), (5), and (6) suggest that there is an imbalance between O 2 and CO 2 in the algal-bacterial system for complete BPA biodegradation. These results concur with previous studies, which Table 1 found that higher levels of O 2 were required in the algalbacterial system for complete biodegradation of more reduced pollutants such as methane and methanol compared with glucose (Bahr et al 2011). For this reason, some researchers suggest that an external O 2 or CO 2 supply is necessary in an algal-bacterial system for recalcitrant pollutant removal (Bordel et al 2009;Bahr et al 2011).…”
Section: Carbon Mass Balancesupporting
confidence: 92%
“…(4), (5), and (6) suggest that there is an imbalance between O 2 and CO 2 in the algal-bacterial system for complete BPA biodegradation. These results concur with previous studies, which Table 1 found that higher levels of O 2 were required in the algalbacterial system for complete biodegradation of more reduced pollutants such as methane and methanol compared with glucose (Bahr et al 2011). For this reason, some researchers suggest that an external O 2 or CO 2 supply is necessary in an algal-bacterial system for recalcitrant pollutant removal (Bordel et al 2009;Bahr et al 2011).…”
Section: Carbon Mass Balancesupporting
confidence: 92%
“…To the best of our knowledge, this is the first time that a coupling of these processes has been directly shown for a natural anoxic environments. Interestingly, microbial consortia of photosynthetic algae and MOB are employed in oxygen-deficient wastewater treatment plants to remove methane (Bahr et al, 2011;van der Ha et al, 2011van der Ha et al, , 2012. In the environment, this mechanism might occur in permanently and seasonally stratified lakes as well as marine basins such as the Black Sea, where light penetrates to the anoxic chemocline.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of organic carbon degradation and assimilation by microorganisms is an important, but unresolved question in understanding and predicting microbial activities in soils and sediments (Bahr et al, 2011). Free energy, molecular structure, and redox state of organic compounds have been proposed as major factors governing the sequence of their utilization (Bahr et al, 2011). Glucose, lactate and acetate have different free energies and molecular structure, and are the most commonly employed OC sources for denitrification.…”
Section: Effects Of Organic Carbon and Initial Nitrate Concentration mentioning
confidence: 99%